PENGARUH JENJANG PENDIDIKAN, SKALA USAHA DAN LAMA USAHA TERHADAP PENGGUNAAN INFORMASI AKUNTANSI PADA UMKM DI KECAMATAN CIAWIGEBANG - Awanda Nirwana; Dendi Purnama (Program Studi Akuntansi, Universitas Kuningan, 2019)
This research aims to analyze the effect of education levels, business scale and length of business on the use of accounting information. The population in this study were all MSMEs in Ciawigebang sub-district as many as 380 MSMEs. While the sample in this study were 79 MSMEs using the slopin formula and random probability with the provision of sample proportions. The data analysis technique used in this study is multiple regression analysis.Based on the results of the study indicate that the level of education, business scale, and duration of business have a significant positive effect on the use of accounting information. Thus, the level of education, business scale and duration of business are determinants of the use of accounting information on MSMEs. Keywords: use of accounting information, education level, business scale, length of business